On the vertical handoff performance for interworking between microcellular and macrocellular networks - Salamah, Muhammed; Tansu, Fatma (IEEE Computer Society, 2006)
The next generation wireless network environments are expected to support anywhere, anytime connectivity for high-performance applications like multimedia, full-motion video and high data rates with appropriate quality of service (QoS). To provide a solution to these demanding needs, service providers intend to combine different technologies in heterogeneous networks. In this study, upward and downward vertical handoff performance is studied on interworking between microcellular and macrocellular networks. We primarily proposed an efficient strategy for the execution of vertical handoff decision with the aim of maximizing the QoS experienced by the user. In the proposed strategy, we concentrated on crucial features like user preference and support of different service types. Simulation results on the key parameters such as Grade of Service (GoS), throughput and resource utilization prove that the proposed strategy can provide powerful support for QoS in heterogeneous networks. © 2006 IEEE.
2nd International Conference on Wireless and Mobile Communications, ICWMC 2006 --
Keywords: Computer simulation; Multimedia systems; Optimization; Parameter estimation; Quality of service; Telecommunication services; Data rates; Heterogeneous networks; Macrocellular networks; Vertical handoff performance; Wireless networks